Angiomyxoma Presenting as an Unusual Vaginal Mass - Alam, Irin Parveen; Pervin, Zebunnesa; Monayem, Farhana Binte (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Angiomyxoma is a rare tumour which arises from pelvis. A case of an Angiomyxoma of vagina in a 35year old lady is reported. The patient was presented with a mass about 7×8 cm coming down through introitus and urinary discomfort. Mass was dissected out and Histopathological examination revealed angiomyxoma. Though it is a rare tumour it is clinically misdiagnosed with vaginal polyp, vaginal cyst or inversion of uterus. J Bangladesh Coll Phys Surg 2014; 32: 229-230